Elevated International Normalized Ratio Is Associated With Ruptured Aneurysms. Issue 9 (September 2018) - Can, Anil; Castro, Victor M.; Dligach, Dmitriy; Finan, Sean; Yu, Sheng; Gainer, Vivian; Shadick, Nancy A.; Savova, Guergana; Murphy, Shawn; Cai, Tianxi; Weiss, Scott T.; Du, Rose
Abstract : Background and Purpose—: The effects of anticoagulation therapy and elevated international normalized ratio (INR) values on the risk of aneurysmal subarachnoid hemorrhage are unknown. We aimed to investigate the association between anticoagulation therapy, elevated INR values, and rupture of intracranial aneurysms. Methods—: We conducted a case-control study of 4696 patients with 6403 intracranial aneurysms, including 1198 prospective patients, diagnosed at the Massachusetts General Hospital and the Brigham and Women's Hospital between 1990 and 2016 who were on no anticoagulant therapy or on warfarin for anticoagulation. Patients were divided into ruptured and nonruptured groups. Univariable and multivariable logistic regression analyses were performed to evaluate the association of anticoagulation therapy, INR values, and presentation with a ruptured intracranial aneurysm, taking into account the interaction between anticoagulant use and INR. Inverse probability weighting using propensity scores was used to minimize differences in baseline demographics characteristics. The marginal effects of anticoagulant use on rupture risk stratified by INR values were calculated. Results—: In unweighted and weighted multivariable analyses, elevated INR values were significantly associated with rupture status among patients who were not anticoagulated (unweighted odds ratio, 22.78; 95% CI, 10.85–47.81 and weighted odds ratio, 28.16; 95% CI, 12.44–63.77). In anticoagulated patients, warfarin use interacts significantly with INR when INR ≥1.2 by decreasing the effects of INR on rupture risk. Conclusions—: INR elevation is associated with intracranial aneurysm rupture, but the effects may be moderated by warfarin. INR values should, therefore, be taken into consideration when counseling patients with intracranial aneurysms. Abstract : Supplemental Digital Content is available in the text.